2015
DOI: 10.3389/fpsyg.2015.01627
|View full text |Cite
|
Sign up to set email alerts
|

Motor and cognitive growth following a Football Training Program

Abstract: Motor and cognitive growth in children may be influenced by football practice. Therefore the aim of this study was to assess whether a Football Training Program taken over 6 months would improve motor and cognitive performances in children. Motor skills concerned coordinative skills, running, and explosive legs strength. Cognitive abilities involved visual discrimination times and visual selective attention times. Forty-six children with chronological age of ∼9.10 years, were divided into two groups: Group 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 26 publications
(28 reference statements)
0
34
0
4
Order By: Relevance
“…Chaddock et al (2010a) conducted a study on children aged 9 and 10 demonstrating that physical activity is able to increase the volume of the striatum, one of the structures belonging to base ganglia which are related to both the motor and cognitive tasks, in particular regarding attentive functions. Th e same research group (Chaddock et al, 2010b) demonstrated through functional magnetic resonance a positive correlation between increased hippocampal volume and mnestic performance in pre-adolescent children who performed regular exercise (Alesi et al, 2015). Whiteman, Young, Budson, Stern and Schon (2016) further demonstrated how aerobic activity aff ects a particular area in the hippocampus called the entorhinal cortex.…”
Section: Physical Activity and Cognitive Processes: What Changes In "mentioning
confidence: 92%
See 1 more Smart Citation
“…Chaddock et al (2010a) conducted a study on children aged 9 and 10 demonstrating that physical activity is able to increase the volume of the striatum, one of the structures belonging to base ganglia which are related to both the motor and cognitive tasks, in particular regarding attentive functions. Th e same research group (Chaddock et al, 2010b) demonstrated through functional magnetic resonance a positive correlation between increased hippocampal volume and mnestic performance in pre-adolescent children who performed regular exercise (Alesi et al, 2015). Whiteman, Young, Budson, Stern and Schon (2016) further demonstrated how aerobic activity aff ects a particular area in the hippocampus called the entorhinal cortex.…”
Section: Physical Activity and Cognitive Processes: What Changes In "mentioning
confidence: 92%
“…In the last twenty years, research regarding the eff ects of movement on the brain in children and adolescents has increased (Alesi et al, 2015). According to these studies, motor activities should gain a signifi cant role in preventing metabolic, respiratory, and cardiovascular diseases as well as in the ability to support, increase and re-activate the cognitive processes useful for each type of learning.…”
Section: Physical Activity and Cognitive Processes: What Changes In "mentioning
confidence: 99%
“…[1012] For example, Alesi and her research team found that with an improvement in motor skills after physical training, executive functions (attention) improved correspondingly in a group of children with typical development. [10,11] The same motor-cognitive connection was observed in children with atypical development (Down syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…Given the variety of exercise-related contexts available, however, exercise practice is far more than just a way for enhancing cardiovascular fitness 17 . In fact, given its inherent and varying perceptual and cognitive demands, it is expected that cognitive enhancement would follow sustained practice 18 . For instance, optimal performance in football or basketball requires, together with a sufficiently good level of fitness, rapid adaptation and response to the constantly varying exercise environment (i.e., they are instances of externally-paced activities).…”
Section: Introductionmentioning
confidence: 99%